Optimization of the polysaccharide extraction process from Rosa roxburghii Tratt using Box-Behnken response surface methodology and monosaccharide composition analysis - ZHAN,Qingqing (2022)
Abstract Rosa roxburghii Tratt polysaccharide (RRTP) has various physiological functions that benefit the human body. Therefore, improving the extraction rate of RRTP is of crucial for its promotion and application. In this study, RRTP was extracted using an intermittent ultrasound-assisted enzymatic method, and the effects of five factors on the extraction rate of RRTP were studied using a single factor test and response surface methodology. The regression equation model was significant and had good reliability, and the enzyme concentration, liquid-solid ratio and ultrasonic temperature exhibited a positive and significant effect on the RRTP content. The optimal extraction conditions were a power of 360 W, an enzyme concentration of 2.0%, a liquid-solid ratio of 40 mL/g, an ultrasonic temperature of 60 °C and an ultrasonic time of 25 min. Under these conditions, the crude polysaccharide of RRT (CRRTP) yield was 15.03%, and the RRTP content was 4.50%. The RRTP comprised mannose, rhamnose, galacturonic acid, glucose, galactose and arabinose with molar percentages of 3.39%, 2.91%, 26.73%, 35.16%, 21.21% and 10.61% by High Performance Liquid Chromatography (HPLC), respectively. These results suggested that the intermittent ultrasonic-assisted enzymatic method can improve the extraction rate of RRTP.